The Manufacturing Sector in Argentina, Brazil, and Mexico Transformations and Challenges in the Industrial Core of Latin America - Santarcángelo, Juan Eduardo (Palgrave Studies in Latin American Heterodox Economics, 2019)
XIX, 199 p. 59 illus.